EFFORTS TO SELECT TECHNOLOGICAL ALTERNATIVES FOR FLOOD CONTROL IN THE CIREBON RAYA AREA - Oktavia Sukhatama, Yohana
Cirebon, as part of the industrial areas in the Rebana Triangle, will become one of the metropolitan areas as well as an economic center on the island of Java because it is projected as a Special Economic Zone (KEK). The development plan for this area will certainly have an impact on the economy and the development of the community in the area. However, development efforts will also have an impact on land use change, which will certainly have an impact on the ability of the environment to adapt. One of the problems that will arise is an increase in cases of flooding in this area. The level of vulnerability to flooding is influenced by aspects based on natural factors, including meteorological factors such as aspects of rainfall and watershed characteristics, including aspects of slope, elevation, soil type, soil permeability, and land use. Spatial analysis was carried out on aspects of the flood vulnerability level using scoring, weighting, and overlaying the aspect map so that information on the contribution of each aspect to the flood vulnerability level was obtained: 14% rainfall, 17% slope, 18% elevation, 18% land use, 16% soil type, and 17% soil permeability. The majority of the Cirebon Raya area was also discovered to be vulnerable and highly susceptible to flooding. The selection of flood control technology in the Cirebon area was carried out using the Analytical Hierarchy Process (AHP) method. Based on the results of the AHP method, water and soil conservation measures were selected as alternative actions that are prioritized in flood control. Then, based on the results of an analysis of the aspects that influence the level of vulnerability to flood events in the Cirebon Raya area, the most suitabel implementation alternative to be implemented tends to be in the form of control efforts, including land management in the Cirebon Raya area.